Technology in retrospect : social studies in the information age, 1984-2009 - Diem, Richard A.; Berson, Michael J. (International social studies forum, the series., 2010)
January 2009 marked the 25th anniversary of one of the most famous three minutes of television history. It was during half-time of the 1984 Super Bowl that APPLE show cased its new Macintosh Computer in an avant-guard commercial. In the following three weeks sales of the new computer, in both the public and private sectors, took off leading some to note this occasion as the "true" start of the information age. At the same time schools joined this so-called information revolution and began to use the new technology, in various forms, in a much more serious manner.Given both the changing nature of technology, as well as its classroom applications, over the past quarter century this work's goal is to capture the historical trends of both use and application of information technology in the social studies during this era. This is done by providing a retrospective view , from 1984 through 2009 , of where we've been, where we are, and a view of new tools and strategies and possible studies that are emerging that can enhance our understanding of the effects that technology has and will have on the social studies.